2001
DOI: 10.3354/dao046109
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity of aquabirnavirus strains to various marine fish species

Abstract: To determine the infectivity of marine birnavirus (MABV) in various marine fish species, experimental infection was performed in combination groups of 5 fish species with 7 strains of MABV and 1 strain of infectious pancreatic necrosis virus (IPNV). Mortality was observed in yellowtail Seriola quinqueradiata and amberjack S. dumerili infected with MABV strains Y-6, Y-10K and H-1, but not in other infected species. MABV was reisolated from most combination groups, but the virus isolation rate and virus infectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
1
19
0
1
Order By: Relevance
“…Although all specimens showed no symptoms of viral infection, ABVs were detected regardless of host fish species. MABV can infect various fish species without clinical signs with relatively low virus titers in the infected fish (23). Our results showed that some fish with no symptoms have ABVs at a comparatively high concentration.…”
Section: Discussionmentioning
confidence: 75%
“…Although all specimens showed no symptoms of viral infection, ABVs were detected regardless of host fish species. MABV can infect various fish species without clinical signs with relatively low virus titers in the infected fish (23). Our results showed that some fish with no symptoms have ABVs at a comparatively high concentration.…”
Section: Discussionmentioning
confidence: 75%
“…12 Such a quarantine system could be implemented in conjunction with RT-PCR testing of the sentinel fish or of some of the new arrivals, similar to what was done in the current study. Only after the batch of fish has been determined to be free of ABV infection, would the fish be released into the general population.…”
mentioning
confidence: 99%
“…19 Because any fish in the aquarium can potentially carry pathogens, preventive steps should be taken. Thus, it is recommended that aquariums quarantine all new arrivals with specific pathogen-free (SPF) sentinel fish, such as makogarei (or marbled flounder, Pseudopleuronectes yokohamae) or yellowtail, which are susceptible to MABV, 12 before transferring the new arrivals to the display.…”
mentioning
confidence: 99%
“…MABV was first isolated from diseased yellowtail Seriola quiqueradiata in Japan in 1985 (Sorimachi & Hara 1985). Similar birnaviruses have been isolated from shellfish and other cultured and wild fish from around the world (Sohn et al 1995, Cutrin et al 2000, Isshiki et al 2001). Many of the birnavirus isolates were genetically similar , suggesting that all isolates belong to the MABV group.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the birnavirus isolates were genetically similar , suggesting that all isolates belong to the MABV group. MABVs have a broad host range in various marine organisms (Cutrin et al 2000, Isshiki et al 2001.…”
Section: Introductionmentioning
confidence: 99%